40. SURVEY THE IN-PATIENT'S SATISFACTION WITH QUALITY OF NURSING CARE AT DISTRICT 7 HOSPITAL (Tạp chí Y học Cộng đồng, 2024)
Bachkground: Satisfaction is generally considered the emotional state brought about by the customer assessment and attitude in using the services. Quality nursing care characterized as competence and personal caring. To ensure patient satisfaction, nurses need to provide personalized care. Therefore, we investigated this study and aimed to survey the in-patient's satisfaction with the quality of nursing care.Methods: A cross sectional correlation design involving in-patients who live in hospitals at least 2 days and maximum 30 days. The participants (N =350) who answered questionnaire that was used to determine the nursing care quality and the in-patient's satisfaction. Linear Regression and Pearson Correlation were used to find the relationship between patients' satisfaction and Nursing Care Quality.Result: In-patient's satisfaction was improved about 60.4% by Nursing Care Quality and decreased by the facilities in the hospital.Conclusion: To improve Nursing Care Quality, the nurses need to improve the skills such as Nurse's Care, Nurse's empathy, Nurse care patient, Nurse professional training, Nurse interest Patient's question.
Keywords: Patient satisfaction; Quality of nursing care; Nursing care evaluation